Diurnal changes in analgesic requirement - (:unkn) unknown (My University, 1999)
The aim of this study was to find out 24 hour profile of epidural analgesic requirement of postoperative patients retrospectively. Epidural analgesia records of ASA I-II, 20-60 years old, 192 patients who had lumber epidural catheters placed preoperatively for per and postoperative analgesia were analysed retrospectively. Epidural opioid boluses were injected according to patients' requests and recorded injection times were counted hourly in order to establish 24 hour profile of postoperative analgesic requirements. There were very significant differences in analgesic requirement (p<0.05). Analgesic request number was highest (average request was 61.7 per hour) between 19.00 and 01.00 and lowest (average request was 25.6 per hour) between 02.00 and 07.00 o'clock. Also analgesic request had peaks at 09.00, 11.00 and 15.00 o'clock. When we compared 24 hour profile of analgesic requirement and normal ACTH secretion, diurnal changes of analgesic requirement seemed to be inversely correlated with hormones like ACTH and β- endorphine.
Keywords: Analgesic requirement; Diurnal changes; Epidural; Opioids